The bleeding heart: A case of cardiac angiosarcoma presenting with pulmonary hemorrhage and hemoptysis - Maher Marar, MD; Saad Mohammad, MD; Ahmad Abdulraheem, MD; Munther Hammad, MD; Sa’ed Al Hayek, MD (Radiology Case Reports, 2025)
Primary cardiac angiosarcoma is an extremely rare and aggressive tumor that originates from the endothelial lining of cardiac blood vessels. We report a case of a 48-year-old man with history of military burn pit exposure, who presented with shortness of breath, cough, and hemoptysis. He was treated as a case of pneumonia, later he developed a diffuse pulmonary hemorrhage, and the etiology of his symptoms was found to be cardiac angiosarcoma with lung involvement. This case highlights the important clinical, radiological, and pathological characteristics of a rare cancer that commonly spreads to the lungs, urging healthcare providers to keep it in mind when diagnosing hemoptysis and pulmonary hemorrhage.